Development of a Mobile-Based Microlearning Application as a Learning Media at SMA IT UlilÂ AlbabÂ Batam - Handayani, Siskha; Nasrullah, Muchamad Fajri Amirul; Sibagariang, Swono; Feby, Feby; Yulius, Rina; Widyastuti, Hilda; Nizan, Muhamad Sahrul; Failasuf, Banu; Afif, Iqbal (Politeknik Negeri Batam, 2024)
In the digital era, the integration of technology in education has become increasingly important to create more effective and engaging learning experiences. The implementation of microlearning in education makes the learning time more effective and efficient. Microlearning delivers knowledge or information in small, digestible chunks, enabling learners to easily absorb, understand, and remember the content. Ulil Albab Integrated Islamic High School (SMAIT Ulil Albab) Batam is a formal educational institution located in Batam, Riau Islands. The learning media currently used by the school include books, photos, videos, and PowerPoint presentations. This community service activity aims to assist the school in developing a mobile-based microlearning media that can provide a more engaging learning experience and make students' learning time more effective and efficient. The methods used include preparation stages such as literature study and needs analysis, implementation stages like developing the microlearning application, and the final stages such as socialization and training. The results of the application testing showed that user satisfaction with the mobile-based microlearning application was 87.52% in the very satisfied category. Meanwhile, the evaluation of partner satisfaction with the community service activity revealed that the partner was very satisfied with the conducted activity, with a satisfaction percentage of 90.3%.